2004
DOI: 10.5194/angeo-22-3741-2004
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the interaction between two ejecta in the interplanetary medium: one- and two-dimensional hydrodynamic simulations

Abstract: Abstract.We studied the heliospheric evolution in one and two dimensions of the interaction between two ejecta-like disturbances beyond the critical point: a faster ejecta 2 overtaking a previously launched slower ejecta 1. The study is based on a hydrodynamic model using the ZEUS-3-D code. This model can be applied to those cases where the interaction occurs far away from the Sun and there is no merging (magnetic reconnection) between the two ejecta. The simulation shows that when the faster ejecta 2 overtake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…The inclusion of the first CME was needed to match observed values of the hydrodynamic parameters at 1 AU, even though the two CMEs have not fully interacted by 1 AU. The propagation and interaction of two ejecta from 18 R to 1 AU have also been recently modeled using a two-dimensional hydrodynamic code (Gonzalez-Esparza et al 2004). Schmidt & Cargill (2004) studied the interaction of two CMEs in the LASCO coronographs' fields of view (1.7Y32 R ) using 2.5-dimensional MHD simulations; the authors investigated different scenarios with and without direct magnetic interactions between the flux ropes.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of the first CME was needed to match observed values of the hydrodynamic parameters at 1 AU, even though the two CMEs have not fully interacted by 1 AU. The propagation and interaction of two ejecta from 18 R to 1 AU have also been recently modeled using a two-dimensional hydrodynamic code (Gonzalez-Esparza et al 2004). Schmidt & Cargill (2004) studied the interaction of two CMEs in the LASCO coronographs' fields of view (1.7Y32 R ) using 2.5-dimensional MHD simulations; the authors investigated different scenarios with and without direct magnetic interactions between the flux ropes.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamical response and ensuing geoeffectiveness of these structures are directly associated with the interaction during their formation and evolution. Numerical simulations have been applied to study most of the complex structures: e.g., the interaction of a shock wave with an MC [ Vandas et al , 1997; Odstrcil et al , 2003; Xiong et al , 2006], and the interaction of two MCs [ Odstrcil et al , 2003; Gonzalez‐Esparza et al , 2004; Lugaz et al , 2005; Wang et al , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…[2] However, the interaction between two CMEs close to the Sun [Gopalswamy et al, 2001[Gopalswamy et al, , 2002 and between magnetic clouds near the Earth [see, e.g., Burlaga et al, 2001;Berdichevsky et al, 2003;Gonzalez-Esparza et al, 2004;Farrugia et al, 2006a;and ' Xie et al [2006] studied 37 long-lived geomagnetic storms (LLGMS events) with Dst < À100 nT and the associated CMEs which occurred during 1998-2002 and found that 24 of 37 events were caused by successive CMEs and number of interacting magnetic clouds was observed from 2 up to 4.…”
mentioning
confidence: 99%
“…[2] However, the interaction between two CMEs close to the Sun [Gopalswamy et al, 2001[Gopalswamy et al, , 2002 and between magnetic clouds near the Earth [see, e.g., Burlaga et al, 2001;Berdichevsky et al, 2003;Gonzalez-Esparza et al, 2004;Farrugia et al, 2006a; and references therein] has been reported. A number of papers showed that several strong magnetic storms (see, for instance, events on 31 March, 2001, minimum Dst value of À387 nT, 11 -13 April, 2001, Dst min = À271 nT [Wang et al, 2003]; 28-30 October, 2003, Dst min = À363 nT [Veselovsky et al, 2004;Skoug et al, 2004];20 November, 2003, Dst min = À472 nT [Ermolaev et al, 2005]; 8 -10 November, 2004, Dst min = À373 nT [Yermolaev et al, 2005]) have been generating by multiple interacting magnetic clouds.…”
mentioning
confidence: 99%